Work Engagement among Rescue Workers: Psychometric Properties of the Portuguese UWES - Sinval, Jorge; Marques-Pinto, Alexandra; Queirós, Cristina; Marôco, João (Frontiers in Psychology, 2018)
Rescue workers have a stressful and risky occupation where being engaged is crucial to go behind of physical and emotional risks to help other persons. This study aims to estimate engagement levels of rescue workers (namely comparing nurses, firefighters, and police officers) and to assess the validity evidence related to the internal structure of the Portuguese versions of the UWES-17 and UWES-9, namely, dimensionality, measurement invariance between occupational groups, and reliability of the scores. To evaluate the dimensionality, we compared the fit of the three-factor model with the fit of a second-order model. A Portuguese version of the instrument was applied to a convenience sample of 3,887 rescue workers (50% nurses, 39% firefighters and 11% police officers). Engagement levels were moderate to high, with firefighters being the highest and nurses being the lowest engaged. Psychometric properties were evaluated in the three-factor original structure revealing acceptable fit to the data in the UWES-17, although the UWES-9 had better psychometric properties. We considered the observed statistically significant correlations between the three original factors, and proposed a 2nd hierarchal structure that we named engagement. The UWES-9 first-order model obtained full uniqueness measurement invariance, and the second-order model obtained partial (metric) second-order invariance.